2006
DOI: 10.1038/sj.cgt.7700946
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus 1 (HSV-1) for cancer treatment

Abstract: Cancer remains a serious threat to human health, causing over 500 000 deaths each year in US alone, exceeded only by heart diseases. Many new technologies are being developed to fight cancer, among which are gene therapies and oncolytic virotherapies. Herpes simplex virus type 1 (HSV-1) is a neurotropic DNA virus with many favorable properties both as a delivery vector for cancer therapeutic genes and as a backbone for oncolytic viruses. Herpes simplex virus type 1 is highly infectious, so HSV-1 vectors are ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 215 publications
1
104
0
Order By: Relevance
“…Theoretical considerations and experimental observations made thus far indicate that mechanisms of tumor resistance to HSV-1 therapy include ECM-mediated impairment of intratumoral virus spread, impaired viral entry into tumor cells because of decreased expression of HSV-1 entry receptors, inhibition of viral replication after viral entry into tumor cells, and virus clearance by the host immune system. [5][6][7][12][13][14][15][17][18] In this study, we found that at least two of these potential mechanisms of virus resistanceimpaired virus spread in the ECM and inhibition of viral replication after viral entry into tumor cells-are also relevant to 3D tumor cell cultures.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Theoretical considerations and experimental observations made thus far indicate that mechanisms of tumor resistance to HSV-1 therapy include ECM-mediated impairment of intratumoral virus spread, impaired viral entry into tumor cells because of decreased expression of HSV-1 entry receptors, inhibition of viral replication after viral entry into tumor cells, and virus clearance by the host immune system. [5][6][7][12][13][14][15][17][18] In this study, we found that at least two of these potential mechanisms of virus resistanceimpaired virus spread in the ECM and inhibition of viral replication after viral entry into tumor cells-are also relevant to 3D tumor cell cultures.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5][6] Oncolytic HSV-1 therapy is dependent on virus replication in tumor cells and is augmented by host antiviral and infection-induced anti-tumor immune responses. [7][8][9][10][11] In spite of significant progress, oncolytic virotherapy faces significant challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used TK for gene therapy studies is HSV-TK in combination with an acycloguanosine such as ganciclovir which has been tested in a series of pre-clinical and clinical trials in a wide range of cancer types. 111,112 The potential exists to improve this study by combining it with multi-modality imaging techniques such as SPECT, PET or MRI. Combined application of the imaging modalities and imaging probes will maximize the diagnostic and therapeutic potential of bacterial gene therapy and achieve a targeted regime for cancer therapy with minimal off-target effects.…”
Section: Combined Imaging and Therapymentioning
confidence: 99%
“…This strategy, also called prodrugactivating gene therapy, offers the potential for selective tumor destruction without inducing significant systemic toxicity. 9,10 The thymidine kinase (TK) from herpes simplex virus (HSV) is the best characterized suicide gene. 11 Expression of functional HSV-TK in transduced cells has the ability to transform a nontoxic prodrug such as ganciclovir (GCV) into a toxic phosphorylated (GCVtriphosphate) compound that competes with triphosphate as a substrate for DNA polymerase.…”
Section: Introductionmentioning
confidence: 99%